Pengelompokan Potensi Produksi Buah-Buahan di Provinsi Sumatera Utara dengan Menerapkan K-Clustering (Studi Kasus : Dinas Tanaman Pangan dan Holtikultura) - Herna Mahulae (STMIK Budi Darma, 2020)
Until now the agricultural sector still plays an important role in the national economy. Fruits are commercial commodities which are very strategic to be developed and traded in regional, national and international markets. So that the optimal conditions in an area for the production of commodity types of fruit is a very important comparative advantage. Based on data on fruit production results in the Office of Food and Horticultural Crops of North Sumatra showing several regions with varying amounts of fruit yields. For this reason, grouping of potential fruit-producing regions is needed to be based on the names of districts / cities that have the potential to produce fruit. By using the K-Means Clustering Method, the division of regional groups can be done based on the harvested area (Ha), production (tons) and the year of harvest. In this research, clustering of fruit-producing potential areas was carried out using the K-Means algorithm. By using K-Means aims to facilitate the grouping of an area in knowing the level of potential based on districts / cities in the province of North Sumatra